(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: The informal economy is an important phenomenon in developing countries. In recent years there has been an increasing policy interest in the informal economy and its poverty dynamics. Objective: This paper explores the relationship between the informal economy and poverty through literature review of internet based open access resources published from 2000 to 2019. Method: Many empirical studies in our review have shown that informal employment has a causal impact on household poverty. This paper seeks to evaluate how informal economy through the theoretical lens applied to real world problems and explore the potential value of empirical evidences in progressing new understandings of the linkage between informal economy and poverty. Findings: Informal economy is the main source of livelihood for marginalized and poor and earnings from this sector have had a strong impact on the household livelihood. It is important that policymakers recognize the informal economy as a positive contribution to poverty, especially in countries where formal economic activities are less in operation. Conclusions: This study identifies the role of informal economy in poverty dynamics and important policy debates which provide directions to improve the quality and consistency for future research.